PENGARUH CITRA KANDIDAT TERHADAP PARTISIPASI POLITIK MASYARAKAT DALAM PELAKSANAAN PEMILU DI DESA DONGKALA KECAMATAN PASARWAJO KABUPATEN BUTON - Muna Amalia; La Asiri; Junaid Gazalim; Roni Amaludin (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to examine the influence of candidate image on public political participation during the election in Dongkala Village, Buton Regency, Southeast Sulawesi Province. The research employed a quantitative approach using simple linear regression analysis. The findings reveal that candidate image has a significant effect on political participation, with a correlation coefficient of 0.744, indicating a strong and positive relationship, and a coefficient of determination (R²) of 0.554, meaning that 55.4% of the variation in political participation can be explained by the candidate’s image. The t-test shows that the candidate image significantly affects political participation, and the F-test confirms that the regression model is appropriate for prediction. These results highlight the crucial role of candidate image in encouraging public engagement in the democratic process. It is recommended that candidates and election organizers strengthen political communication that fosters trust and closeness with the community. Future research could expand the scope of variables to gain a more comprehensive understanding of the factors influencing political participation